SOSIOLOGI OLAHRAGA SEBAGAI SARANA PEMBENTUKAN KARAKTER ANAK MUDA - Rian Andriansyah; Tito Parta wibowo; Raden Atqo; Rendi Mulyadi; Ahmad Rizal; Dafa Hakim; M Rizki; N Destriana; Zakiyah Rahman; Wahyudi Wahyudi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Character education through sport is becoming increasingly important in the face of dynamic socio-cultural change. The sociology of sport offers an approach to understanding sport as a social phenomenon that has a broad impact on youth character building. This research uses a descriptive qualitative method to explore the role of sport in youth character building through a sociology of sport approach. The results showed that sport can be a medium for socialization, value internalization, and identity formation. Participation in sports activities can form a physically healthy, mentally strong, and morally sound young generation. However, sports can also be a space for reproduction of negative values if not balanced with constructive social values. Therefore, the sociology of sport approach can offer strategic solutions in designing sports programs that not only pursue achievements, but also form Indonesian people with character. This research is expected to contribute to the development of character education through sports and increase awareness of the importance of the sociology of sport in shaping young people with character and integrity.